Safahat majhulah min tarikh al-harakah al-islamiyyah al-mu'asirah : (Markaz al-Mahrusah, 2006)
'Unknown pages from the history of the modern Islamic movement : from the Defeat to the gallows : the testimony of Talal Al-Ansari' Islam.